2021
DOI: 10.1055/s-0041-1736298
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Maternal Folic Acid Supplementation with the Autism Spectrum Disorder: A Systematic Review

Abstract: Objective To analyze the scientific production regarding maternal folic acid (FA) supplementation and its relationship with autistic spectrum disorder (ASD). Data Sources We performed unrestricted electronic searches in the BIREME virtual bank, Virtual Health Library (VHL) and Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed) databases. Selection of Studies For sample selection, articles that met the proposed objectives were included, published in English, Spanish and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Studies have evaluated fetal exposure to folic acid and the biology (DNA methylation, hypomethylation, imprinting, and epigenetics) of neonatal childhood neurodevelopmental disorders but have not yet determined any benefit or risk. 45 A scoping review suggested that inadequate nutrient intake during pregnancy was associated with brain and neuro-behavioral deficits, and that future studies should establish and quantify the benefits of maternal nutrition during pregnancy on neurodevelopment and recommend adequate supplementation. 46 Murray et al 47 reviewed the risks of high-dosage supplementation of folic acid during pregnancy, including in animal models.…”
Section: Obesitymentioning
confidence: 99%
“…Studies have evaluated fetal exposure to folic acid and the biology (DNA methylation, hypomethylation, imprinting, and epigenetics) of neonatal childhood neurodevelopmental disorders but have not yet determined any benefit or risk. 45 A scoping review suggested that inadequate nutrient intake during pregnancy was associated with brain and neuro-behavioral deficits, and that future studies should establish and quantify the benefits of maternal nutrition during pregnancy on neurodevelopment and recommend adequate supplementation. 46 Murray et al 47 reviewed the risks of high-dosage supplementation of folic acid during pregnancy, including in animal models.…”
Section: Obesitymentioning
confidence: 99%
“…Prescribing folic acid as a prophylactic measure to prevent adverse outcomes in live births is widely endorsed and substantiated in the literature. Beyond its role in preventing neural tube defects ( Martinez et al, 2021 , van Gool et al, 2018 ), there are reports of its potential in averting early placental rupture, prematurity, reducing low birth weight, preventing cardiac anomalies, brain tumors, and even mitigating autism risk in early childhood ( Al-mashhadane and Amer, 2018 , Sampaio et al, 2021 , van Gool et al, 2018 ). However, a cohort of researchers aims to discern potential adverse effects of folic acid supplementation during preconception and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid supplementation is widely endorsed for preventing birth-related complications, including neural tube defects ( Martinez et al, 2021 , van Gool et al, 2018 ). It also contributes to averting issues like early placental rupture, prematurity, low birth weight, cardiac anomalies, brain tumors, and even reducing autism risk in early childhood ( Al-mashhadane and Amer, 2018 , Sampaio et al, 2021 , van Gool et al, 2018 ). However, some studies suggest a potential association between folic acid supplementation and respiratory diseases in newborns and children, including wheezing, asthma, respiratory allergies, and bronchitis ( Al-mashhadane and Amer, 2018 , Guo et al, 2019 , Nasir et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gangguan spektrum autisme (autism spectrum disorders; ASD) merupakan gangguan perkembangan saraf yang kompleks pada anak, yang dapat menyebabkan berbagai masalah pada interaksi sosial dan komunikasi serta perilaku repetitif dan restriktif dengan tingkat keparahan gejala penyakit yang bervariasi dari satu pasien ke pasien lainnya (Lord et al, 2018;CDC, 2021;Zeidan et al, 2022). Penderita ASD ditandai dengan adanya defisit dalam interaksi sosial, keterampilan komunikasi verbal dan nonverbal, hipersensitivitas sensorik, dan kesulitan menyesuaikan diri dengan perubahan yang tidak terduga, serta pola perilaku, minat, atau aktivitas yang terbatas dan berulang (American Psychiatric Association, 2013;CDC, 2021;Hoxha et al, 2021;Sampaio et al, 2021;Salari et al, 2022). ASD umumnya dapat didiagnosis sejak usia 18-24 bulan, dimana pada usia inilah gejala karakteristik dapat dibedakan dari perkembangan normal dan dari keterlambatan atau kondisi perkembangan lainnya (Zeidan et al, 2022).…”
Section: Pendahuluanunclassified